Incorporating Medical Museum Specimens Into the Training of Environmental Health Students - Sotirios Maipas; Sofia Liossi; Anastasia Konstantinidou; Marlen Mouliou; Andreas C Lazaris; Effie Papageorgiou; Nikolaos Kavantzas (SAGE Publishing, 2023)
Xenobiotics, radiation, and other environmental health risk factors leave their mark on human organs. This can be demonstrated through the use of pathology museum specimens. Upon completing two semesters of postgraduate studies in environmental health, a tour of the Museum of Pathology is offered to postgraduate students at Athens Medical School who are being trained in environmental health. A structured questionnaire is employed to assess the specimens' impact on several aspects: improving students' observational skills, reinforcing the taught material, acquiring new relevant knowledge, and cultivate the social-cognitive ability of empathy. Additionally, students are asked to evaluate the necessity of preserving metadata associated mainly with the social context of the specimens. This research-educational initiative, a component of an ongoing larger project, underscores the significant educational and research value of museum specimens pertaining to environmental health. Furthermore, effectively utilizing such exhibits can enrich the museum experience for visitors and increase public awareness of environmental health issues.